The Effect of Increasing Chicken Manure Levels in Supplemental Diets for Lactating Galla Goats on Milk Production - Nyakalo, M.S. Badamana; Wanyoike, M. (1989)
A feeding trial, with 4 treatments replicated 3 times, to determine the usefulness of utilizing poultry waste as a protein source for ruminants was conducted using 84 lactating Galla goats which were each offered Chloris gayana hay ad libitum supplemented with 500g of concentrates. Four concentrate diets were formulated. The diets composed of maize germ, wheat bran, molasses, and poultry waste constituting 0, 15, 30 and 45% of the total mixture replacing cotton seed cake as a convetional protein source. Milk yield, liveweight changes and diet acceptability were monitored. All rations were consumed equally well regardless of poultry waste content. Total milk yield including or excluding the quantity suckled by the kids as well as liveweight changes showed no significant differences (P>0.05) among the treatments. However, there was a strong tendency toward higher milk yields from goats fed a diet containing 15% poultry waste. High weighing errors to determine the kids' residual milk intakes might have influenced these results, hence suggesting a possible limitation in the use of the Weigh -Suckle - Weigh method. Animals in Treatment IV produced higher milk yield, though for reasons not established yet, than those in Treatment III and slightly less than those in the control. It suffices to conclude that in the advent of either partial or total scarcity of a conventional protein source, poultry waste would be an effective replacement. Although, all animals appeared to lose weight during the experimental period, goats in treatment two, considerably lost more liveweight than the others as lactation progressed, but differences were not significant (P>0.05).